MENYOAL LEGALITAS NIKAH SIRRI (ANALISIS METODE ISTIṢLĀḤIYYAH) - Fakhria, Sheila (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Siri marriage (unregistered marriage) is the one that has met the terms and pillars that have been established by the Islamic law and have been strengthened by the opinion of the classical Moslem scholars. Siri marriage is no longer able to achieve the function of the Islamic pillarsand terms of marriage, especially the witnesses of marriage, which aims to announce a marriage as a guarantee of the rights for the bride, the bride's family and the society. The consideration of siri marriage today is the benefits. This article confirms that marriage registration is a large-scale of the witness's position to achieve the objective of the witness to the society. Thus, marriage is no longer only performed as the terms and pillars that are established by the Moslem scholars, but it also involves the state in order to guarantee the rights of the parties concerned in order to achieve the aim of marriage that is sakinah, mawaddah and raḥmah. This article discusses the effort to re-examine the existence of the siri marriage in the perspective of one methodology of the principles of Islamic jurisprudence that is the method of istislahiah reasoning.[Nikah sirri merupakan pernikahan yang telah memenuhi syarat dan rukun yang telah ditetapkan oleh hukum Islam serta dikuatkan oleh pendapat ulama klasik. Nikah sirri tidak lagi mampu untuk mencapai fungsi dari rukun dan syarat perkawinan terutama saksi yang bertujuan untuk mengumumkan perkawinan sebagai penjaminan hak bagi mempelai, keluarga mempelai serta masyarakat. Pertimbangan nikah siri pada masa sekarang adalah kemaslahatan. Artikel ini menegaskan bahwa pencatatan perkawinan merupakan skala besar dari kedudukan saksi untuk mencapai tujuan saksi pada masyarakat. Dengan demikian, pernikahan tidak lagi hanya dilaksanakan sebagaimana syarat dan rukun yang ditetapkan oleh ulama akan tetapi juga melibatkan negara demi menjamin hak-hak pihak yang berkaitan demi mencapat tujuan perkawinan yaitu sakinah, mawaddah dan raḥmah. Artikel ini membahas tentang upaya menelaah kembali eksistensi nikah sirri dalam sudut pandang salah satu metodologi usul fikih yaitu metode penalaran istislahiah.]